DEVELOPMENT OF COGNITIVE AND PSYCHOMOTOR EVALUATION INSTRUMENTS FOR TRANSAXLE, MOTOR, AND GENERATOR REPLACEMENT (ATIKANOTO: Journal of Automotive Engineering Education, 2024)
As technology advances, competencies must also keep pace with these developments. The current trend in the automotive sector is the transition from electric vehicles to electric vehicles. In electric vehicle competencies, there is no evaluation instrument that can be used to measure electric vehicle maintenance competencies. The impact of this is a non-objective assessment. This study aims to create a valid and feasible cognitive and psychomotor evaluation instrument for replacing transaxles, motors, and generators. The research method used in creating this instrument is 4D (Define, Design, Development, Disseminate). The results of the study show that based on the content validity test on the cognitive evaluation instrument with the CVR and CVI techniques, out of 45 evaluation instrument items, 2 of them are invalid. Based on the construct validity test, the level of difficulty is obtained with a moderate and difficult level, the discrimination power of 27 questions is very good, 13 are quite good, 3 questions are set aside/revised, the distractor index is known in several question choices that need to be revised. Based on the reliability test, the results of the Spearman Brown correlation coefficient of 0.768 can be stated that the cognitive evaluation instrument is reliable. Based on the content validity test on the psychomotor evaluation instrument using the CVR and CVI techniques, it was found that all items were declared valid. The conclusion of this study is that the cognitive and psychomotor evaluation instrument for replacing transaxles, motors, and generators is valid and suitable for use.Seiring dengan berkembangnya teknologi, kompetensi juga harus mengikuti perkembangan tersebut. Perkembangan tren yang terjadi yang terjadi pada bidang otomotif saat- sat ini adalah transisi kendaraan menjadi electric vehicle. Pada kompetensi kendaraan listrik, belum terdapat instrument evaluasi yang dapat digunakan untuk mengukur kompetensi perawatan kendaraan listrik. Dampak dari hal tersebut adalah  penilaian yang tidak objektif. Penelitian ini bertujuan untuk membuat Instrumen evaluasi kognitif dan psikomotor penggantian Transaxle, motor, dan generator yang valid dan layak digunakan. Metode penelitian yang digunakan pada pembuatan instrumen ini adalah 4D (Define, Design, Development, Disseminate). Hasil Penelitian menunjukkan berdasarkan uji validitas isi pada instrument evaluasi kognitif dengan teknik CVR dan CVI, dari 45 butir soal instrument evaluasi 2 diantaranya tidak valid.  Berdasarkan uji validitas construct diperoleh tingkat kesukaran dengan tingkat sedang dan sukar, Daya beda terdapat 27 soal baik sekali, 13 cukup baik, 3 soal disisihkan/revisi, indeks pengecoh diketahui pada beberapa pilihan soal harus dilakukan revisi. Berdasarkan uji reliabilitas didapatkan hasil koefisien korelasi spearman brown sebesar 0.768 yang dapat dinyatakan bahwa instrumen evaluasi kognitif reliable. berdasarkan uji validitas isi pada instrument evaluasi psikomotor dengan teknik CVR dan CVI, diperoleh bahwa seluruh item dinyatakan valid. Kesimpulan dari penelitian ini adalah Instrumen evaluasi kognitif dan psikomotor penggantian Transaxle, motor, dan generator yang valid dan layak digunakan.